Origin of the neonatal gut microbiota and probiotic intervention: a randomized controlled trial - Li, Zhe; Zhang, Yiwen; Tan, Xiaozhi; Kian Deng, Tye; Gao, Qian; Xiao, Xiaomin; Xu, Chengfang (Frontiers in Nutrition, 2024)
Objective This study aims to evaluate the origin of the neonatal gut microbiota on the 14th day and probiotic intervention in the third trimester. Methods Samples were obtained from a total of 30 pregnant individuals and their offspring, divided into a control group with no intervention and a probiotic group with live combined Bifidobacterium and Lactobacillus tablets, analyzing by 16S rRNA amplicon sequencing of the V4 region to evaluate the composition of them. Non-metric multidimensional scaling and SourceTracker were used to evaluate the origin of neonatal gut microbiota. Results We found that the microbiota in the neonatal gut at different times correlated with that in the maternal microbiota. The placenta had more influence on meconium microbiota. Maternal gut had more influence on neonatal gut microbiota on the 3rd day and 14th day. We also found that the maternal gut, vaginal, and placenta microbiota at full term in the probiotic group did not have a significantly different abundance of Bifidobacterium, Lactobacillus, or Streptococcus. However, some other bacteria changed in the maternal gut and their neonatal gut in the probiotic group.